2016
DOI: 10.1021/acs.inorgchem.6b02509
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Molecular Magnesium Hydride Featuring a Terminal Magnesium–Hydrogen Bond

Abstract: The reactivity of the molecular magnesium hydride [Mg(MeTACD·AlBu)H] (1) featuring a terminal magnesium-hydrogen bond and an NNNN-type macrocyclic ligand, MeTACD ((MeTACD)H = Me[12]aneN = 1,4,7-trimethyl-1,4,7,10-tetraazacyclododecane), can be grouped into protonolysis, oxidation, hydrometalation, (insertion), and hydride abstraction. Protonolysis of 1 with weak Brønsted acids HX such as terminal acetylenes, amines, silanols, and silanes gave the corresponding derivatives [Mg(MeTACD·AlBu)X] (X = C≡CPh, 3; HN(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…Compounds 7 and 8 , like 6 , are poorly soluble even in polar organic solvent (~3 mg mL −1 in THF at ambient temperature), and show broadened signals in their 1 H NMR spectra, particularly so for 7 . Nevertheless, with a facile route to amido-beryllium hydride complexes established, we sought to study reactivity towards CO 2 and CO, particularly given previously reported reactivity of heavier group 2 hydrides towards these important carbon building blocks 15 , 17 , 34 , 35 . Suspensions of 6 in toluene completely dissolve over the course of 30 min when stirred under an atmosphere of CO 2 , leading to 1 H NMR spectra indicating the presence of two species, both of which appear to contain a formate C- H moiety, in a 7:3 ratio ( δ = 7.69 and 7.83 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 7 and 8 , like 6 , are poorly soluble even in polar organic solvent (~3 mg mL −1 in THF at ambient temperature), and show broadened signals in their 1 H NMR spectra, particularly so for 7 . Nevertheless, with a facile route to amido-beryllium hydride complexes established, we sought to study reactivity towards CO 2 and CO, particularly given previously reported reactivity of heavier group 2 hydrides towards these important carbon building blocks 15 , 17 , 34 , 35 . Suspensions of 6 in toluene completely dissolve over the course of 30 min when stirred under an atmosphere of CO 2 , leading to 1 H NMR spectra indicating the presence of two species, both of which appear to contain a formate C- H moiety, in a 7:3 ratio ( δ = 7.69 and 7.83 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, 1 H NMR spectroscopy demonstrates that both [κ 3 -Tism Pr i Benz ]­ZnH and [Tism Pr i Benz ]­MgH react rapidly with CO 2 , and the magnesium formate complex, [Tism Pr i Benz ]­Mg­(κ 2 -O 2 CH) ( 3 ), has been structurally characterized by X-ray diffraction (Figure ). However, despite this observation, additional studies suggest that the direct insertion of CO 2 into the M–H bond is not part of the catalytic cycle.…”
mentioning
confidence: 99%
“…An IR band due to ῡ (C≡C) was recorded at 2057 cm -1 , while the 13 C { 1 H} NMR spectrum showed two resonances at 134.2 and 113.7 ppm due to the alkynyl carbon atoms, in agreement with literature values. 21 Formation of complex 4 as in Scheme 3 can therefore be viewed as a Brönsted-Lowry acid-base reaction involving strongly basic Mo-H bonds (for PhC≡CH in DMSO pKa=28.7). 22 At this stage, however, no mechanistic information is available.…”
mentioning
confidence: 99%